Answer: (1,-2) (0,-3)
Step-by-step explanation:
brainliest plz
quantity 8 times b raised to the twelfth power end quantity over a raised to the ninth power
1 over quantity 6 times a raised to the ninth power times b raised to the twelfth power end quantity
1 over quantity 8 times a raised to the ninth power times b raised to the twelfth power end quantity
Answer:
Step-by-step explanation:
Answer:To simplify the expression "a raised to the negative third power over quantity 2 times b raised to the fourth power end quantity all cubed", we can follow these steps:
Step 1: Simplify the numerator.
a raised to the negative third power is equivalent to 1 over a cubed.
Step 2: Simplify the denominator.
2 times b raised to the fourth power is equivalent to 2b to the fourth power.
Step 3: Combine the simplified numerator and denominator.
So, the expression becomes 1 over a cubed divided by 2b to the fourth power, all cubed.
Step 4: Simplify the division.
When we divide by a fraction, we can multiply by its reciprocal.
The reciprocal of 2b to the fourth power is 1 over 2b to the fourth power.
Therefore, the expression simplifies to 1 over a cubed times 1 over the reciprocal of 2b to the fourth power, which is 1 over 2b to the fourth power.
In summary, the simplified expression is 1 over 2b to the fourth power times a cubed.
y=5x+38
B. 32
C. 44
D. 48
It would be Choice "B"
Answer:
5
Step-by-step explanation:
if ax^2 +bx + c ====>discriminant formula is b^2 - 4ac from the quadratic formula
x2 + 3x + 1 = 0
Then;
a=1
b=3
c=1
b^2 - 4ac = 3^2 -4*1*1
= 9-4
= 5